If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 88 = -4(1 + -6n) + -1n 88 = (1 * -4 + -6n * -4) + -1n 88 = (-4 + 24n) + -1n Combine like terms: 24n + -1n = 23n 88 = -4 + 23n Solving 88 = -4 + 23n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-23n' to each side of the equation. 88 + -23n = -4 + 23n + -23n Combine like terms: 23n + -23n = 0 88 + -23n = -4 + 0 88 + -23n = -4 Add '-88' to each side of the equation. 88 + -88 + -23n = -4 + -88 Combine like terms: 88 + -88 = 0 0 + -23n = -4 + -88 -23n = -4 + -88 Combine like terms: -4 + -88 = -92 -23n = -92 Divide each side by '-23'. n = 4 Simplifying n = 4
| https://www.mathsonline.com.au/assets/interactives/images/3247-103-2.png | | k/4-k=8 | | 8x+2-2x=44 | | 2+5*7= | | 2x+12=-28-6 | | 0.2x=-0.6+1.7x | | 1.1=0.2X | | 2+2m=4 | | -3*1/3 | | 8m-6=5m+9 | | 5m+3.5=-2m+2.5 | | w(3w-1)=102 | | 3-(x-7)/2=9 | | 1.14=0.2X | | 4t-6=2r+18 | | 10(2+x)=50 | | 14(1-y)= | | 3x-5+7+7x-9=12x+8-23x+6 | | 8y-12=6y+8 | | 5(6-7x)=-75 | | 6m+5n-3+12= | | 4x^4-x^2-24x+10=0 | | 3(10-4x)=45 | | -2x-69=21-5x | | 5x(-6)=3x(-8) | | J-3+4j=7 | | -3n+-6=-18 | | 3(4x+13)=51 | | -73-8x=7x-30x | | -3/4x=9/10 | | 7m-2m+11m=48 | | 4(5x+7)=16 |